2021
DOI: 10.1038/s41419-020-03324-w
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomotropic agents including azithromycin, chloroquine and hydroxychloroquine activate the integrated stress response

Abstract: The integrated stress response manifests with the phosphorylation of eukaryotic initiation factor 2α (eIF2α) on serine residue 51 and plays a major role in the adaptation of cells to endoplasmic reticulum stress in the initiation of autophagy and in the ignition of immune responses. Here, we report that lysosomotropic agents, including azithromycin, chloroquine, and hydroxychloroquine, can trigger eIF2α phosphorylation in vitro (in cultured human cells) and, as validated for hydroxychloroquine, in vivo (in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 78 publications
(88 reference statements)
0
28
0
Order By: Relevance
“…Many chemotherapeutic and lysosomotropic agents cause cell death by inducing apoptosis 4 , 30 . However, MPM-1 did not induce any of the signs that are typically associated with apoptosis, such as exposure of phosphatidylserine, chromatin condensation or depolarized mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Many chemotherapeutic and lysosomotropic agents cause cell death by inducing apoptosis 4 , 30 . However, MPM-1 did not induce any of the signs that are typically associated with apoptosis, such as exposure of phosphatidylserine, chromatin condensation or depolarized mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…To test if AZM-induced cytotoxicity correlates with lysosomes, we performed live-cell confocal microscopy using pH-sensitive LysoTracker as a specific dye for lysosomes. 7,8 Similar with chloroquine (CQ), AZM caused markedly enlarged, dilatate, and accumulated lysosomes (Figure 3E). Expression of lysosomal associated membrane protein 2 (LAMP2), a specific marker for lysosomes, was significantly enhanced in AZM-treated iPSC-CMs (Figure 3F,G), whereas cathespin D expression was unchanged (Figure S16).…”
Section: F I G U R E 1 Electrophysiological Effects Of Acute Azithromycin (Azm) In Induced Pluripotent Stem Cell-derived Cardiomyocytes (mentioning
confidence: 89%
“…In addition to CQ/HCQ, several other lysosomotropic agents have been investigated. One example is azithromycin, a commonly used antibiotic that has similar lysosomotropic property as CQ/HCQ and this pharmacology effect is related to its antibacterial and antiviral function 349,350 . Recent work has indicated that azithromycin is able to block the entry of SARS‐CoV‐2 via disruption of the fusion process between viral and vacuolar membranes, a process related to its lysosomotropic property 351 .…”
Section: Implication Of Autophagy In Health and Diseasesmentioning
confidence: 99%
“…One example is azithromycin, a commonly used antibiotic that has similar lysosomotropic property as CQ/HCQ and this pharmacology effect is related to its antibacterial and antiviral function. 349,350 Recent work has indicated that azithromycin is able to block the entry of SARS-CoV-2 via disruption of the fusion process between viral and vacuolar membranes, a process related to its lysosomotropic property. 351 Moreover, numerous clinical trials have been conducted, using either azithromycin alone or in combination with CQ/HCQ in treatment of COVID-19.…”
Section: 43mentioning
confidence: 99%